Characterization of Curtovirus V2 Protein, a Functional Homolog of Begomovirus V2 - Luna, Ana P.; Romero-Rodríguez, Beatriz; Rosas-Díaz, Tábata; Cerero, Laura; Rodríguez-Negrete, Edgar A.; Castillo, Araceli G.; Bejarano, Eduardo R. (Frontiers in Plant Science, 2020)
Geminiviruses are plant viruses with circular, single-stranded DNA genomes packaged within geminate particles. Among the Geminiviridae family, Begomovirus and Curtovirus comprise the two best characterized genera. Curtovirus and Old World begomovirus possess similar genome structures with six to seven open-reading frames (ORF). Among them, begomovirus and curtovirus V2 ORFs share the same location in the viral genome, encode proteins of similar size, but that show extremely poor sequence homology between the genera. V2 from Beet curly top virus (BCTV), the model species for the Curtovirus genus, as it begomoviral counterpart, suppresses post-transcriptional gene silencing (PTGS) by impairing the RDR6/SGS3 pathway and localizes in the nucleus spanning from the perinuclear region to the cell periphery. By aminoacid sequence comparison we have identified that curtoviral and begomoviral V2 proteins shared two hydrophobic domains and a putative phosphorylation motif. These three domains are essential for BCTV V2 silencing suppression activity, for the proper nuclear localization of the protein and for systemic infection. The lack of suppression activity in the mutated versions of V2 is complemented by the impaired function of RDR6 in Nicotiana benthamiana but the ability of the viral mutants to produce a systemic infection is not recovered in gene silencing mutant backgrounds. We have also demonstrated that, as its begomoviral homologue, V2 from BCTV is able to induce systemic symptoms and necrosis associated with a hypersensitive response-like (HR-like) when expressed from Potato virus X (PVX)-derived vector in N. benthamiana, and that this pathogenicity activity does not dependent of its ability to supress PTGS.